Modes of metabolic compensation during mitochondrial disease using the Drosophila model of ATP6 dysfunction. - Alicia M Celotto; Wai Kan Chiu; Wayne Van Voorhies; Michael J Palladino (PLoS ONE)
Numerous mitochondrial DNA mutations cause mitochondrial encephalomyopathy: a collection of related diseases for which there exists no effective treatment. Mitochondrial encephalomyopathies are complex multisystem diseases that exhibit a relentless progression of severity, making them both difficult to treat and study. The pathogenic and compensatory metabolic changes that are associated with chronic mitochondrial dysfunction are not well understood. The Drosophila ATP6(1) mutant models human mitochondrial encephalomyopathy and allows the study of metabolic changes and compensation that occur throughout the lifetime of an affected animal. ATP6(1)animals have a nearly complete loss of ATP synthase activity and an acute bioenergetic deficit when they are asymptomatic, but surprisingly we discovered no chronic bioenergetic deficit in these animals during their symptomatic period. Our data demonstrate dynamic metabolic compensatory mechanisms that sustain normal energy availability and activity despite chronic mitochondrial complex V dysfunction resulting from an endogenous mutation in the mitochondrial DNA. ATP6(1)animals compensate for their loss of oxidative phosphorylation through increases in glycolytic flux, ketogenesis and Kreb's cycle activity early during pathogenesis. However, succinate dehydrogenase activity is reduced and mitochondrial supercomplex formation is severely disrupted contributing to the pathogenesis seen in ATP6(1) animals. These studies demonstrate the dynamic nature of metabolic compensatory mechanisms and emphasize the need for time course studies in tractable animal systems to elucidate disease pathogenesis and novel therapeutic avenues.